Postburn Elevation in Fibrin Degradation Product is Related to Burn Severity - Barua, Prasun; Iqbal, Mohammed Kaisar; Haque, Mahmudul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Burn is reported to cause significant alteration of haemocoagulativeparameters, but due to lack of proper understanding of burn coagulopathy, only theroutine coagulation tests are generally used, even though these provide limiteddiagnostic or prognostic information about burns and postburn complications. So,this study specifically aimed to characterize the changes in plasma FibrinDegradation Product (FDP) together with routine coagulative parameters and theirrelations with burn-severity. Materials and methods: This cross-sectional comparative study was carried out inthe Department of Biochemistry and Department of Burn and Plastic Surgery ofChattogram Medical College Hospital from January to December in 2014. 130subjects of 18 – 65 years enrolled in two groups by nonprobability consecutivesampling. Group-A consisted of 80 patients with minor, moderate and major burnsas per American Burn Association severity classification, whereas Group-B included50 age and sex-matched healthy subjects. Plasma FDP was estimated by immunoturbidimetricmethod in STA compact automated analyser. Bleeding Time (BT),Clotting Time (CT) and Prothrombin Time (PT) were also determined using standardmethods. Results: Burn patients had significantly higher mean FDP (10.13 ± 5.63 μg/ml) thancontrols (2.50 ± 1.56 μg/ml) which increased with increase in burn-severity (4.83,8.12 and 15.48 μg/ml in minor, moderate and major burns respectively). PlasmaFDP increased in 91.25% burn patients. While BT and CT were mostly unchanged, PTwas prolonged in 66.25% burn patients (Mean = 15 seconds) but that did not seemto correlate with burn-severity or with FDP.Conclusion: Plasma FDP increased significantly in burn patients showing better andconsistent correlation with burn-severity than routine coagulation parameters. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 43-46